EXPORT ENHANCEMENT PLAN OF COCONUT SHELL CHARCOAL BRIQUETTE BY PT. INDRATMA SAHITAGUNA SEMARANG - Ghea Olivia Noora Sanjaya; Jozef Bambang Tri Joga; Budi Prasetya (Politeknik Negeri Semarang, 2016)
Coconut shell charcoal briquettes export has great prospect both from theabundant raw materials availability and the huge world market import quantity.PT. Indratma Sahitaguna Semarang utilizes this briquette to be used as analternative fuel substitute for oil, gas, and fuel wood that has not been developedby the industry.This research was carried out to analyze the coconut shell charcoal briquettesexport prospects, its production improvement, raw material inventory control, andthe marketing activities undertaken to meet the briquette export prospects by PT.Indratma Sahitaguna Semarang in 2017.The data in this research is historical data from 2011 to 2015. The obtained datasources are from PT. Indratma Sahitaguna Semarang, the FAO UN, Badan PusatStatistik, journals, books, and other sources. The analysis techniques used in thisresearch are descriptive analysis with trend calculation and Economic OrderQuantity (EOQ) Method.This study shows that PT. Indratma Sahitaguna Semarang has a bright andpromising prospect of exporting coconut shell charcoal briquettes. In order toprevent excess quantity of product, this company preferably uses a moderateproduction patterns so that the excess quantity of product in a given month can beallocated to production in the previous month to be used as finished goodsinventory.PT. Indratma Sahitaguna Semarang is expected to save Total Cost (TC) of Rp260,175,764 when applying Economic Order Quantity (EOQ) method forplanning during 2017. In order to achieve the export prospect, this companypreferably conducts marketing activities using STP Strategy.